2014
DOI: 10.1371/journal.pone.0086364
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties and Membrane-Active Mechanism of a Potential α-Helical Antimicrobial Derived from Cathelicidin PMAP-36

Abstract: Antimicrobial peptides (AMPs), which present in the non-specific immune system of organism, are amongst the most promising candidates for the development of novel antimicrobials. The modification of naturally occurring AMPs based on their residue composition and distribution is a simple and effective strategy for optimization of known AMPs. In this study, a series of truncated and residue-substituted derivatives of antimicrobial peptide PMAP-36 were designed and synthesized. The 24-residue truncated peptide, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
136
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(154 citation statements)
references
References 52 publications
12
136
0
1
Order By: Relevance
“…However, in another study of H-(LARL) 3 -(LARL) n series, hemolytic activity increased, while antimicrobial activity decreased with increasing peptide chain length (Niidome et al 2005). Other work in our lab has shown that the 24-residue-truncated derivative of PMAP-36 displays antimicrobial activity comparable to the parental peptide; however, further truncation of the peptide significantly decreases its antimicrobial activity (Lv et al 2014). Based on these lines of evidence, the relationship between peptide length and antimicrobial potency is not linear, and there seems to be a threshold effect.…”
Section: Discussionmentioning
confidence: 68%
“…However, in another study of H-(LARL) 3 -(LARL) n series, hemolytic activity increased, while antimicrobial activity decreased with increasing peptide chain length (Niidome et al 2005). Other work in our lab has shown that the 24-residue-truncated derivative of PMAP-36 displays antimicrobial activity comparable to the parental peptide; however, further truncation of the peptide significantly decreases its antimicrobial activity (Lv et al 2014). Based on these lines of evidence, the relationship between peptide length and antimicrobial potency is not linear, and there seems to be a threshold effect.…”
Section: Discussionmentioning
confidence: 68%
“…Antimicrobial peptides (AMPs) are currently being studied extensively to assess their use as a new class of antimycotics because they possess broad-spectrum antimicrobial activities and may possibly thwart resistance (13)(14)(15). Chromogranin A is a major soluble protein of the adrenal medullary chromaffin granules and neurons, and is conservative in mammals (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported the potent activity of PMAP-36 and its analogs against gram-negative and gram-positive bacterial strains15, while the antifungal effects and potential mechanisms are poorly understood. Therefore, in addition to determining antibacterial activities, we measured the in vitro antifungal properties of PMAP-36 and its derivatives against Candida in the present study.…”
mentioning
confidence: 99%